Role of Venoarterial Extracorporeal Membrane Oxygenation in Cardiogenic Shock Secondary to Takotsubo Syndrome: A Case Series - Niu H; Chen M; Liang H; Li J; Cai S (International Journal of Women's Health, 2025)
Haiming Niu, Miaolian Chen, Hongkai Liang, Jianwei Li, Shaoqing Cai Department of Critical Care Medicine, Zhongshan People’s Hospital, Zhongshan, People’s Republic of ChinaCorrespondence: Shaoqing Cai, Department of Critical Care Medicine, Zhongshan People’s Hospital, 2 Sunwen Dong Road, Zhongshan, 528400, People’s Republic of China, Email zxpcai@163.comBackground: Takotsubo syndrome (TTS) is an acute, self-limiting disease characterized by left ventricular wall motion abnormalities and apical ballooning. The incidence of cardiac shock (CS) during the acute phase of TTS is a major cause of mortality. We reviewed three female patients with TTS due to different causes, all of whom rapidly progressed to CS as the main clinical manifestation.Case Presentation: Case 1: A 28-year-old female developed chest pain after receiving the human papillomavirus vaccine, which quickly led to shock and cardiac arrest. Coronary angiography showed no obstructive lesions and left ventriculography indicate left ventricular hypokinesis in the anterior wall, apex, and inferior wall. Her blood pressure was difficult to maintain with medication, and venoarterial extracorporeal membrane oxygenation (VA-ECMO) was initiated. Five days later, her cardiac function improved, and VA-ECMO was discontinued. Case 2: A 54-year-old female experienced chest pain following severe anxiety due to family issues, which quickly progressed to CS. Coronary angiography revealed no obstructive lesions and left ventriculography showed significantly reduced wall motion and spherical expansion in the apex and anterior wall. Shock and pulmonary edema were refractory to medication, so VA-ECMO support was provided. Five days later, her cardiac function recovered, and VA-ECMO was weaned off. Case 3: A 40-year-old female presented with a headache and quickly developed dyspnea, followed by refractory shock. Coronary angiography showed no obstructive coronary lesions; echocardiography suggested general wall motion abnormalities, particularly in the apex and middle segments, consistent with apical ballooning syndrome. VA-ECMO was initiated in the emergency department, and an abdominal computerized tomography scan suggested a possible pheochromocytoma. Seven days later, her cardiac function improved, and VA-ECMO was decannulated.Conclusion: Vaccination, anxiety, or pheochromocytoma can all potentially trigger TTS complicated by CS. VA-ECMO is a promising option for patients with TTS complicated by CS.Keywords: takotsubo syndrome, venoarterial extracorporeal membrane oxygenation, vaccine, anxiety, pheochromocytoma, case series